Knowledge transfer in Digital Twins: the methodology to develop Cognitive Digital Twins - D’Amico, Rosario Davide; Sarkar, Arkopaul; Karray, Mohamed Hedi; Addepalli, Sri; Erkoyuncu, John Ahmet (Elsevier, 2024)
In the realm of Digital Twins (DTs), industry experts have emphasised the pivotal concept of the Federation of Twins, envisioning seamless collaboration across sectors driven by shared semantics. In response to this challenge, the Cognitive Digital Twin (CDT) integrates the DT framework with formal semantics, specifically ontologies. This paper introduces a comprehensive five-step methodology for CDT development. Furthermore, it becomes possible to incorporate human expertise into the DT ecosystem by adopting an ontological approach. The CDT enhances DT services with advanced reasoning capabilities, leading to a profound semantic enrichment of the data. The presented methodology has been validated using a use case where the CDT is employed to detect malfunctions, significantly reducing manual intervention. This paper advocates for the adoption of CDTs, which represent a harmonious fusion of formal semantics and human expertise, enhancing system efficiency and operational performance.
Keywords: Basic Formal Ontology (BFO); Common Core Ontology (CCO); Connected Digital Twins; Digital Twin; Industrial Ontology Foundry (IOF); Knowledge Graph; Semantics; Top-Level Ontology